2008
DOI: 10.1007/s10895-008-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interaction of Trans-resveratrol with Bovine Serum Albumin: A Fluorescence Quenching Study with Tachiya Model

Abstract: The interaction of trans-resveratrol (TRES) and bovine serum albumin (BSA) was investigated using fluorescence spectroscopy (FS) with Tachiya model. The binding number maximum of TRES was determined to be 8.86 at 293.15 K, 23.42 at 303.15 K and 33.94 at 313.15 K and the binding mechanism analyzed in detail. The apparent binding constants (K (a)) between TRES and BSA were 5.02 x 10(4) (293.15 K), 8.89 x 10(4) (303.15 K) and 1.60 x 10(5) L mol(-1) (313.15 K), and the binding distances (r) between TRES and BSA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 26 publications
10
70
0
Order By: Relevance
“…Table 1 summarizes the results correspondingly calculated results according to equation (1). The values of lgK a are proportional to the number of binding sites (n) (Figure 2), which indicates that the equation (1) used here is suitable to study the interaction between flavonoids and BSA (Berezhkovskiy, 2007;Xiao et al, 2008c). …”
Section: The Binding Constants (K a ) And The Number Of Binding Sitesmentioning
confidence: 84%
“…Table 1 summarizes the results correspondingly calculated results according to equation (1). The values of lgK a are proportional to the number of binding sites (n) (Figure 2), which indicates that the equation (1) used here is suitable to study the interaction between flavonoids and BSA (Berezhkovskiy, 2007;Xiao et al, 2008c). …”
Section: The Binding Constants (K a ) And The Number Of Binding Sitesmentioning
confidence: 84%
“…The quenching of the Trp fluorescence by Zr2-L2 is shown in Figure 2, and similar behavior was observed for the other POMs ( Figures S1-S4). The Tachiya model, presented in Equation (1), was used for analysis of the strength and stoichiometry of the binding [56]:…”
Section: Tryptophan Fluorescence Spectroscopymentioning
confidence: 99%
“…In this study, it was found that HSA was selectively hydrolyzed by Zr(IV)-substituted Lindqvist (( [33,[36][37][38][39]55]. HSA contains one tryptophan residue which is located at position 214, and the use of fluorescence quenching studies are an excellent tool to quantify the strength of the interaction and the number of binding sites for molecules that interact with HSA [56]. A detailed understanding of the parameters responsible for the interaction on a molecular level is necessary to tune the selectivity and rationally design metal-substituted POMs with explicit interaction properties.…”
Section: Introductionmentioning
confidence: 99%
“…These are similar to the interactions of other polyphenols with albumins. [32][33][34][35] Maiti et al 17) indicated an initial hydrophobic association followed by electrostatic interactions as well as van der Waals interactions and hydrogen bonding in the subsequent interacting complex based on thermodynamic parameters using association constants obtained from fluorescence quenching method (ΔG; −29.83~−28.35 kJ/mol, ΔH; −6.76 kJ/mol, ΔS; 73.69 J/mol/K). Our conclusion is somewhat different from theirs, possibly due to the differences in the methodology used.…”
Section: Discussionmentioning
confidence: 99%